Root and leaf decomposition become decoupled over time: implications for below‐ and above‐ground relationships. (16th January 2016) - Ma, Chengen; Xiong, Yanmei; Li, Le; Guo, Dali
Summary: Studies elucidating patterns and mechanisms of decomposition are moving from a leaf‐centred view towards a whole‐plant perspective, in which root and leaf decomposition differs among species, yet this prediction has so far received mixed empirical support. Here, we examined the rates and temporal dynamics of decomposition of absorptive fine roots (the distal two root‐branch orders) and leaf litter by measuring mass loss across 10 subtropical and temperate tree species, and CO2 efflux across 18 tree species in a 15‐month laboratory incubation experiment. Eight of 12 initial chemical traits were positively correlated between roots and leaf litter (Pearson's r range of 0·48–0·82). However, mass loss and respiration rates between roots and leaf litter were correlated only in the first 3 months, but unrelated in the subsequent 12 months. This was due to root decomposition rates slowing down after the first 3 months. The disparity in decomposition rates between roots and leaf litter was mainly due to the higher chemical recalcitrance of roots and suggests that roots and leaf litter need to be considered separately when evaluating their role in plant–soil feedbacks. A better understanding of whole‐plant ecological strategies is needed to quantify the impact roots vs. leaves on detrital processes. Abstract : Lay Summary